Is an excretory urogram mandatory in patients with small to medium-sized renal and ureteric stones treated by extra corporeal shock wave lithotripsy? - Ather, M Hammad (BioMed Central, 2004)
BACKGROUND: An intravenous urogram (IVU) has traditionally been considered mandatory before treating renal and ureteric stones by extracorporeal shock wave lithotripsy (ESWL). This study was designed to see whether there is a difference in complications and the need for ancillary procedures in patients managed by ESWL for renal and ureteric calculi, according to preoperative imaging technique. METHODS: This retrospective study compared 133 patients undergoing ESWL from January 2001 to July 2002. Patients were divided into three groups according to the preoperative imaging technique used: i) IVU; ii) non-contrast enhanced helical computed tomography (UHCT); and iii) ultrasound (US) + X-ray kidney, ureter and bladder (KUB). The groups were matched in terms of age and gender, as well as location, side and size of stones. RESULTS: There was no statistically significantly difference for number of ESWL sessions, number of shock waves and use of ancillary procedures between the three groups. The stone-free rate was 98% for the IVU and UHCT groups, and 97% for the US + X-ray KUB group. CONCLUSIONS: The complication rate and need for ancillary procedures was comparable across the three groups. Patients imaged by UHCT or US + X-ray KUB prior to ESWL for uncomplicated renal and ureteric stones do not require IVU.